Pelatihan Pembuatan Media Pembelajaran dengan Memanfaatkan Bahan Bekas bagi Guru SD Negeri Mangunsari 06 Salatiga - Firosalia Kristin; Yohana Setyawan (Universitas Kristen Satya Wacana Salatiga, 2021)
Media in the teaching and learning process in the classroom is very important. Teachers should be able to create creative and attractive media so that they can motivate students to participate in teaching and learning activities in class well. The objectives of this community service activity are 1) Adding insight to teachers about the nature of learning media and designing instructional media, so that they are motivated to develop learning media according to the characteristics of their students; 2) Provide direct experience for teachers on how to make learning media so that teachers can carry out learning with more quality; 3) Increase the capacity of teachers' skills in developing media independently by utilizing used materials around them. As a result of this service, as many as 60% of teachers considered that community service was very useful for their profession, 33.3% said that the topic of community service was useful for their profession and only 6.7% said that it was not useful for their work. So it can be concluded that this activity is very useful for teachers in making media.